Reproductive responses of primiparous and multiparous Holstein cows submitted to presynch-ovsynch protocol - R.L. Abdel Aziz (Beni-Suef University Journal of Basic and Applied Sciences, 2017)
The specific objective of this study was to determine the reproductive responses of primiparous (n = 446) and multiparous (n = 726) Holstein cows submitted to 12-day presynch-ovsynch protocol under the Egyptian circumstances. Distribution of inter-estrus intervals (IEI) and conception rate to first insemination (FICR) was compared between primiparous and multiparous cows. Furthermore, Seasonal variations of heat detection rate (HDR), conception rate (CR) and pregnancy rate (PR) were investigated. Short IEI tended to be higher in multiparous cows (23.8 vs 20.44%, P = 0.09) compared to primiparous cows. In addition, the incidence of prolonged IEI was decreased from 21.53% in multiparous cows to 16.77% in primiparous cows. On contrary, normal length IEI was 62.78% in primiparous cows, higher than that observed in multiparous cows (54.67%). Moreover, primiparous cows inseminated earlier postpartum (<50 days) achieved higher FICR (31.79%) than multiparous cows (24.46%). Controversially, a tendency toward higher FICR was observed for multiparous cows inseminated after 70 days postpartum (31.89% vs. 23.17%, respectively; P = 0.15). No clear variations in HDR were observed among different seasons, whereas greater CR and PR (P < 0.05) were achieved by cows inseminated during Winter (35.37 and 24.90) and Spring (36.36 and 24.68), compared to those inseminated during Summer (10 and 6.6) and Autumn (21.59 and 15.63). Conceivably, our results demonstrate that primiparous Holstein cows responded better than multiparous cows to the 12-day presynch-ovsynch protocol as evidenced by higher incidence of normal length IEI, lower incidence of short and prolonged IEI and higher FICR. Furthermore, Summer season had significant negative and delayed effects on fertility of Holstein cows submitted to the 12-day Presynch-ovsynch protocol.